Enlightenment the nature: Religious language as an experience of the sensible in the construction of science in the northern tropical Andes - Ponce Solórzano, Paul Javier (2025)
This article, a result of doctoral research, investigates certain conceptualizations, imaginaries, and representations of nature within the context of the emergence of the Enlightenment in the northern tropical Andes, where the territories of present-day Ecuador played a prominent role. This work focuses on the concepts and imaginaries that reveal the meanings associated with the notion of illustrating nature, which encouraged the development of a particular type of knowledge and science. Specifically, the article examines how the produced science in this context was profoundly influenced by an experience in the field of the sensitive, beyond merely utilitarian economic or political purposes. Notably, the sensitive dimension was expressed through religious formulations, which shaped the development of a distinctive science and Enlightenment, different from those of northern Europe, yet achieving significant relevance within the global network of knowledge.